"СЛОВО ЯЗЫКА" Ф.Ф.ФОРТУНАТОВА: ВКЛАД В РАЗВИТИЕ ЛИНГВИСТИЧЕСКОЙ НАУКИ - Елмуратова, С.А. (SCIENCE and SOCIETY, 2025)
F.F.Fortunatov (1848–1912) was an outstanding Russian linguist whose works had a significant impact on the development of Russian and world linguistics. One of the key concepts developed by the scientist is the theory of the "word of language" as a structural unit with independent meaning and a special role in the grammatical system. This article is devoted to the analysis of this theory, its methodological foundations and significance in the modern linguistic context.
Keywords: linguist; language; theory; word form; meaning; concept